Structural and Single Crystal EPR Studies of the Complex Copper L-Glutamine: a Weakly Exchange Coupled System with syn-anti Carboxylate Bridges - Schveigkardt, J. (2002)
We report the molecular structure and a single crystal EPR study at 9.8 and 33.9 GHz of a new copper(II) compound with the amino acid L-Glutamine, Cu[NH2CO2CH(CH2)2CONH2]2. The CuII ion is in an elongated octahedral environment equatorially trans-coordinated by two glutamine molecules acting as bidentate ligands through the nitrogen atom and one oxygen atom of each amino acid group, and axially by two carboxylate oxygen atoms of two neighboring glutamine molecules. Copper ions are arranged in layers connected by syn-anti carboxylate bridges that provide equatorial and apical ligands to the copper ions. Neighboring layers are connected by long chemical paths, which include two amino acid side chains connected by H bonds. Single crystal EPR spectra show a single exchange-collapsed resonance at both microwave frequencies for any magnetic field orientation. The evaluation of the molecular g-tensor from the angular variation of the EPR line position yielded g⊥ = 2.051 and g|| = 2.248, which indicates a dmath image ground orbital for the Cu ions. The angular variation of the EPR line width displays a contribution that is typical of a 2-D magnetic system, and another contribution depending on the microwave frequency, which is attributed to the incomplete collapse of the resonances corresponding to magnetically nonequivalent copper ions. A quantitative analysis of the line width data allowed us to estimate a mean exchange coupling constant |J/k| = 0.42(2) K, which is assigned to the syn-anti carboxylate chemical path that connects neighboring copper ions within a layer. The results are discussed and compared with those observed in similar systems.